Quantitative Flow Ratio or Angiography for the Assessment of Non-culprit Lesions in Acute Coronary Syndromes: Protocol of the Randomized Trial QUOMODO - Ullrich, Helen; Olschewski, Maximilian; Belhadj, Khelifa-Anis; Münzel, Thomas; Gori, Tommaso (Frontiers in Cardiovascular Medicine, 2022)
Background Approximately 50% of the patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndromes (ACS) have additional stenotic lesions in non-infarct-related coronary arteries. The decision whether these stenoses require further treatment is routinely based on angiography alone. The quantitative flow ratio (QFR) is a simple non-invasive method that may help quantify the functional significance of these intermediate coronary artery lesions. The aim of our single-center, randomized superiority trial is to test the impact and efficacy of QFR, as compared to angiography, in the treatment of patients with ACS with multivessel coronary artery disease. Primary goal of the study is to investigate 1. The impact of QFR on the proportion of patients receiving PCI vs. conservative therapy and 2. whether QFR improves angina pectoris and overall cardiovascular outcomes. Methods and Analysis After treatment of the culprit lesion(s), a total of 200 consecutive ACS patients will be randomized 1:1 to angiography- vs. QFR-guided revascularization of non-culprit stenoses. Patients and clinicians responsible are blinded to the randomization group. The primary functional endpoint is defined as the proportion of patients assigned to medical treatment in the two groups. The primary clinical endpoint is a composite of death, non-fatal myocardial infarction, revascularization and significant angina at 12 months. Secondary endpoints include changes in the SAQ subgroups, and clinical events at 3- and 12-month follow-up. Discussion This study is designed to investigate whether QFR-based decision-making is associated with a decrease in angina and an improved prognosis in patients with multivessel disease. Trial Registration Number ClinicalTrials.gov Registry (NCT04808310).